2019
DOI: 10.1111/imcb.12290
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C regulates major histocompatibility complex‐II–peptide presentation and extracellular signal‐regulated kinase‐dependent polarizing cytokine production by bone marrow‐derived dendritic cells

Abstract: Cystatin C is a ubiquitously expressed cysteine protease inhibitor that protects cells from either improper hydrolysis by endogenous proteases or pathogen growth/virulence by exogenous proteases. Although commonly used as a serum biomarker for evaluating renal function, cystatin C is associated with many immunological disorders under various pathophysiological conditions. How cystatin C affects immune cells, especially dendritic cells (DCs), however, is far from clear. In this study, we found that pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
(117 reference statements)
0
23
0
Order By: Relevance
“…CstC, as a cathepsin S inhibitor and regulator, plays a pivotal role in the control of cleavage and removal of the MHC class II invariant chain (Ii) ( 29 , 50 ). It also downregulates the MHC-II chaperon H2-DM, resulting in diminished MHC-II–peptide presentation and reduced T-cell proliferation ( 64 ). CstC and cathepsin S have been shown to contribute to MHC class II antigen processing and presentation ( 11 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CstC, as a cathepsin S inhibitor and regulator, plays a pivotal role in the control of cleavage and removal of the MHC class II invariant chain (Ii) ( 29 , 50 ). It also downregulates the MHC-II chaperon H2-DM, resulting in diminished MHC-II–peptide presentation and reduced T-cell proliferation ( 64 ). CstC and cathepsin S have been shown to contribute to MHC class II antigen processing and presentation ( 11 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also downregulates the MHC-II chaperon H2-DM, resulting in diminished MHC-II–peptide presentation and reduced T-cell proliferation ( 64 ). CstC and cathepsin S have been shown to contribute to MHC class II antigen processing and presentation ( 11 , 64 ). Here, we demonstrated that the silencing of CstC induces a significant increased expression of HLA class II at the cell surface during Mtb infection and coinfection with HIV, but not during HIV mono-infection.…”
Section: Discussionmentioning
confidence: 99%
“…[24]) more closely related to the promyelocytic (HL-60 and U937) or lymphocytic (Jurkat) cells used in the present study. Cystatin C is, for example, taken up by human macrophages [25], and externally added cystatin C has been reported to affect the viability of tuberculosis bacteria in infected macrophages [26] as well as the control of antigen presentation by dendritic cells [27][28][29]. Thus, there is ample evidence indicating that secreted cystatins could also have biological functions intracellularly, in many different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytic activity of vascular DCs was estimated by their uptake of soluble antigens followed by FACS analysis as described before ( 22 ). Briefly, C57BL/6 mice were injected i.v.…”
Section: Methodsmentioning
confidence: 99%